EXPRESSION OF SURFACE MARKERS ON CD4+T-LYMPHOCYTES IN NORMAL PREGNANCY AND PRE-ECLAMPSIA - V. A. Mikhailova (SPb RAACI, 2014)
Abstract. In course of physiological pregnancy, peripheral blood CD4+T-lymphocytes normally migrate to the uterine decidual tissue. Hence, this study aimed to compare expression profiles of adhesion molecules and chemokine receptors on the surface of CD4+T-lymphocytes from peripheral blood in healthy pregnancy and in pre-eclampsia. The amounts of CD4+T-lymphocytes expressing CD184, CD119, CD192, CD197, β7 integrin, CD29, CD49d, CD11b were elevated in healthy pregnant women, as compared with non-pregnant women. The amounts of CD4+T-lymphocytes expressing CD49d, CD44, CD47, as well as intensity of CD47, CD29, CD49d, CD44, Integrin β7, CD54 expression proved to be decreased in cases of preeclampsia when compared with healthy pregnancy. This work was supported by grants ГК N 02.740.11.0711 from Russian Ministry of Education and Science, and Presidential grants НШ-3594.2010.7, МД-150.2011.7.